2011
DOI: 10.1097/nnr.0b013e318221b6ce
|View full text |Cite
|
Sign up to set email alerts
|

Registered Nurses' Job Demands in Relation to Sitter Use

Abstract: High RN overtime and collective inexperience are associated with greater sitter use. A possible explanation is that sitters are used to palliate failures to meet high job demands. Further research is required to assess the impact of sitter use on patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 26 publications
(32 reference statements)
1
21
1
Order By: Relevance
“…More experienced nurses should thus have a broader set of interventions to prevent AEs from occurring. Conversely, when the overall level of experience in a team of nurses is reduced, more AEs may occur [28]. For each patient, nurse experience will be measured as the mean number of years of experience held by all members of the nursing staff who reported work hours on the unit where the patient was hospitalized on a given shift [61].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…More experienced nurses should thus have a broader set of interventions to prevent AEs from occurring. Conversely, when the overall level of experience in a team of nurses is reduced, more AEs may occur [28]. For each patient, nurse experience will be measured as the mean number of years of experience held by all members of the nursing staff who reported work hours on the unit where the patient was hospitalized on a given shift [61].…”
Section: Methodsmentioning
confidence: 99%
“…We recently used digitized payroll data to examine how variations in nurse staffing levels through time are related to the use of patient sitters, a type of unlicensed assistive health care provider (UAP) whose function is to provide close surveillance to patients at risk of an AE [27, 28]. Using a nested case-control approach, we found that patients exposed to higher volumes of overtime hours and to less experienced nursing staff during the antecedent exposure period had a higher likelihood of sitter use compared to controls (Table 1).…”
Section: Pilot Workmentioning
confidence: 99%
“…They are also used for patients who are unable to follow directions or are non-compliant, are at risk to falls, are elopement risks, are violent, have impaired vision and hearing and are deemed to be at risk of removing medical devices. [3][4][5][6][7][8][9] Although most commonly used in hospitals in the United States (U.S.), the practice has been described in hospitals in Saudi Arabia, Australia, Scotland Canada, and Taiwan. A survey of 102 hospitals revealed that all used some form of sitters to provide direct patient surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…[11] One unit in a 600-bed hospital reported a monthly cost of $18,301 and an estimated annual cost of $219,612. [4] Hospitals in the United States have reported spending $500,000 to over $2,000,000 in costs related to sitters. [6,9,12] Clearly, the use of sitters to provide constant surveillance is costly to hospitals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation